mSphere of Influence: Microbiome-Associated Phenotypes Are Modifiable - Michael H. Woodworth (American Society for Microbiology, 2020)
ABSTRACT Michael Woodworth focuses on translational microbiome therapeutic research. In this mSphere of Influence article, he reflects on how “Gut microbiomes of Malawian twin pairs discordant for kwashiorkor” by Michelle Smith et al. (M. I. Smith, T. Yatsunenko, M. J. Manary, I. Trehan, et al., Science 339:548–554, 2013, https://doi.org/10.1126/science.1229000) made an impact on him by revealing the causal influence of microbial communities in the development of severe malnutrition.